The central vein sign in multiple sclerosis patients with vascular comorbidities. (June 2021) - Guisset, François; Lolli, Valentina; Bugli, Céline; Perrotta, Gaetano; Absil, Julie; Dachy, Bernard; Pot, Caroline; Théaudin, Marie; Pasi, Marco; van Pesch, Vincent; Maggi, Pietro
Background: The central vein sign (CVS) is an imaging biomarker able to differentiate multiple sclerosis (MS) from other conditions causing similar appearance lesions on magnetic resonance imaging (MRI), including cerebral small vessel disease (CSVD). However, the impact of vascular risk factors (VRFs) for CSVD on the percentage of CVS positive (CVS + ) lesions in MS has never been evaluated. Objective: To investigate the association between different VRFs and the percentage of CVS + lesions in MS. Methods: In 50 MS patients, 3T brain MRIs (including high-resolution 3-dimensional T2*-weighted images) were analyzed for the presence of the CVS and MRI markers of CSVD. A backward stepwise regression model was used to predict the combined predictive effect of VRF (i.e. age, hypertension, diabetes, obesity, ever-smoking, and hypercholesterolemia) and MRI markers of CSVD on the CVS. Results: The median frequency of CVS + lesions was 71% (range: 35%–100%). In univariate analysis, age ( p  < 0.0001), hypertension ( p  < 0.001), diabetes ( p  < 0.01), obesity ( p  < 0.01), smoking ( p  < 0.05), and the presence of enlarged-perivascular-spaces on MRI ( p  < 0.005) were all associated with a lower percentage of CVS + lesions. The stepwise regression model showed that age and arterial hypertension were both associated with the percentage of CVS + lesions in MS (adjusted R 2  = 0.46; p  < 0.0001 and p  = 0.01, respectively). Conclusion: The proportion of CVS + lesions significantly decreases in older and hypertensive MS patients. Although this study was conducted in patients with an already established MS diagnosis, the diagnostic yield of the previously proposed 35% CVS proportion-based diagnostic threshold appears to be not affected. Overall these results suggest that the presence of VRF for CSVD should be taken into account during the CVS assessment.